(untitled) - Marshak, Stephen (New York, 2001)
Written for students of geology, this text incorporates advances in earth science such as plate tectonics, global warming, and the interconnectivity bewteen the history of Earth and the history of life. It begins with a brief discussion of cosmology and the world's origin.
Keywords: Geology,Địa chất học